HIPOTESIS SAPIR-WHORF DAN STRUKTUR INFORMASI KLAUSA PENTOPIKALAN BAHASA MINANGKABAU - Jufrizal Zul Amri Refnaldi (Program Magister Linguistik Universitas Udayana, 2007)
Abstract Saying as one of the variations of traditional Balinese expressions is one of the forms and practice of language styles used especially in oral commucations. In Balinese society, the formation of this traditional saying is much inspired by the nature phenomena such as the plants, fruit, animals, and manimate objects. The meaning of this saying are closely related to the cultural values, and norms of the Balinenesesociety which relect the interrelationship between the humanbeings and the nature. The cultural values of the saying can be specified as showing the values of educations, moral ethics, and togetherness. All of these values become the orientation of each individual in Balinese society.